Biological implant‐associated granulomatous inflammation resulting in secondary hypercalcemia and azotemia in a dog. Issue 9 (25th July 2018) - Linde, Ken J.; Kelleher, Taylor R.; Perry, James A.
Key Clinical Message: Implant associated granulomatous inflammation causing hypercalcemia can occur following use of commercial xenogeneic pericardial tissue patches in dogs. Removal of the implant can result in resolution of the hypercalcemia, suggesting a causal relationship between the tissue reaction to a xenogeneic implant and development of hypercalcemia. Abstract : Implant associated granulomatous inflammation causing hypercalcemia can occur following use of commercial xenogeneic pericardial tissue patches in dogs. Removal of the implant can result in resolution of the hypercalcemia, suggesting a causal relationship between the tissue reaction to a xenogeneic implant and development of hypercalcemia.